The Commodification of Content, Audiences, and Labor on Instagram Social Media Accounts @raffinagita1717 - Dini Agustina; Udi Rusadi (Jurnal Indonesia Sosial Sains, 2024)
This research aims to analyze the practices of modifying content, audiences, and labors on the Raffinagita1717 Instagram social media account so that it becomes the influencer with the most followers in Indonesia. The formulation of this research problem is the commodification practices of content, audiences, and labors on Raffinagita1717's Instagram social media account. The literature study research method was used in this research. The research results show that the Raffinagita1717 Instagram social media account has commodified content, audiences, and labors to achieve success as an artist with the most followers in Indonesia. Raffi has proven how to maximize the use of Instagram social media by modifying content, audiences, and labors.